2017
DOI: 10.1016/j.ejvs.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Carotid Stenosis Treatment: Variation in International Practice Patterns

Abstract: Despite evidence about treatment options for carotid artery disease, the proportion of asymptomatic patients, treatment modality, and the proportion of women and octogenarians vary considerably among and within countries. There was a significant association of treating more asymptomatic patients in countries with fee for service reimbursement. The findings reflect the inconsistency of the existing guidelines and a need for cooperation among guideline committees all over the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 35 publications
0
35
0
2
Order By: Relevance
“…2,3 Pivotal trials of surgery for recently symptomatic ICA stenosis (North American Symptomatic Carotid Endarterectomy Trial and the European Carotid Surgery Trial) showed that carotid endarterectomy (CEA) resulted in a 7.8% absolute risk reduction of stroke in patients with an ICA stenosis of 50-69% and 15.6% in patients with an ICA stenosis of 70-99% compared to conservative medical treatment. 2,4,5 However, the benefits of surgery were timedependent and diminished rapidly with delay. 2,3 Absolute benefit also increased with age but elderly patients (>80 years) were excluded from the trials.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Pivotal trials of surgery for recently symptomatic ICA stenosis (North American Symptomatic Carotid Endarterectomy Trial and the European Carotid Surgery Trial) showed that carotid endarterectomy (CEA) resulted in a 7.8% absolute risk reduction of stroke in patients with an ICA stenosis of 50-69% and 15.6% in patients with an ICA stenosis of 70-99% compared to conservative medical treatment. 2,4,5 However, the benefits of surgery were timedependent and diminished rapidly with delay. 2,3 Absolute benefit also increased with age but elderly patients (>80 years) were excluded from the trials.…”
Section: Introductionmentioning
confidence: 99%
“…2 Current practice of carotid revascularization was evaluated in 12 countries. 25 Among 58 607 treated cases, the largest national and international variation was seen in indications: overall, about half of the patients were asymptomatic (48%), but this varied from 0% (Denmark) to 73% (Italy). National variation between centres was even bigger and was the highest in Australia (0-72%), Hungary (5-55%), and the USA (0-100%).…”
Section: Revascularizationmentioning
confidence: 99%
“…The recommendations for peripheral revascularization registry data collection were recently created by a modified Delphi approach with on-line interaction within 14 countries among international vascular surgeons and registry mem-bers of the ICVR [19]. The Vascunet and ICVR have additionally performed international benchmarking studies of vascular surgical practice and outcome, identifying important variations in the practice of vascular surgery between countries and regions [20][21][22][23]. These benchmarking studies help to identify clinical areas where further studies are required to reach consensus regarding best management, as well as regional variations which may require focused quality improvement efforts.…”
Section: International Registry Collaborationmentioning
confidence: 99%